2015
DOI: 10.18632/oncotarget.4627
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived cell models as preclinical tools for genome-directed targeted therapy

Abstract: BackgroundIn this study, we established patient-derived tumor cell (PDC) models using tissues collected from patients with metastatic cancer and assessed whether these models could be used as a tool for genome-based cancer treatment.MethodsPDCs were isolated and cultured from malignant effusions including ascites and pleural fluid. Pathological examination, immunohistochemical analysis, and genomic profiling were performed to compare the histological and genomic features of primary tumors, PDCs. An exploratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…Based on that the MCT4 isoform was very strongly expressed in malignant ascites, development of a highly potent MCT4 inhibitor might be effective for treatment of GC with peritoneal carcinomatosis. Our group has previously shown that PDCs are reflective of genomic alterations in patient tumors and clinical phenotypes in response to targeted agents [56]. To the best of our knowledge, this is the first study to systematically investigate the role of MCT4 in malignant ascites using PDCs.…”
Section: Discussionmentioning
confidence: 97%
“…Based on that the MCT4 isoform was very strongly expressed in malignant ascites, development of a highly potent MCT4 inhibitor might be effective for treatment of GC with peritoneal carcinomatosis. Our group has previously shown that PDCs are reflective of genomic alterations in patient tumors and clinical phenotypes in response to targeted agents [56]. To the best of our knowledge, this is the first study to systematically investigate the role of MCT4 in malignant ascites using PDCs.…”
Section: Discussionmentioning
confidence: 97%
“…In cell line factory project in Broad Institute (http://www.broadinstitute.org/cellfactory#home), cells through passage 5 were highlighted. In recent reports, passage 1–4 were analyzed as PDCs1012. These work also emphasized continuous culture to passage 10 to obtain enough cells for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…There have been very few analyses of transcriptomic similarities between cell lines and matched primary cancers. Besides established cell lines, it has been proposed that cancer cells at early passages during cell line establishment (around passage 5, also called patient-derived cells, PDC) may faithfully represent primary cancers101112. Indeed, PDCs were found similar to those of the primary cancers in terms of key gene mutations, copy number profiles and drug responses11.…”
mentioning
confidence: 99%
“…PDC from malignant effusions has more than a few advantages over conventional cell lines [9]. First, PDC models faithfully recapitulated primary patient tumors, with the molecular and gross phenotypic characteristics of the primary tumor retained.…”
Section: Discussionmentioning
confidence: 99%